Single Variable Calculus Questions and Answers

Start Your Free Trial

Single Variable Calculus, Chapter 7, 7.6, Section 7.6, Problem 12

Expert Answers info

eNotes eNotes educator | Certified Educator

calendarEducator since 2007

write13,548 answers

starTop subjects are Math, Literature, and Science

Simplify the expression $\tan \left( \sin^{-1} (x) \right)$

If we let the values of right triangle be...

We know that $\displaystyle \sin \theta = \frac{\text{opposite}}{\text{hypotenuse}} = \frac{x}{1} = x$

$\theta = \sin^{-1}(x)$

And,

$\displaystyle \tan \theta = \frac{\text{opposite}}{\text{adjacent}} = \frac{x}{\sqrt{1-x^2}}$

Thus, $\displaystyle \tan \left( \sin^{-1}(x) \right) = \tan (\theta) = \frac{x}{\sqrt{1-x^2}}$